Salinity and Time Can Alter Epibacterial Communities of an Invasive Seaweed - Saha, Mahasweta; Ferguson, Robert M. W.; Dove, Shawn; Künzel, Sven; Meichssner, Rafael; Neulinger, Sven C.; Petersen, Finn Ole; Weinberger, Florian (Frontiers in Microbiology, 2020)
The establishment of epibacterial communities is fundamental to seaweed health, and fitness, in modulating ecological interactions and may also facilitate adaptation to new environments. Few recent studies have investigated the influence of abiotic factors like light, temperature as drivers of epibacterial community composition on seaweeds. Although salinity can determine bacterial abundance, growth and community composition, influence of salinity as a driver of epibacterial community composition (until species level) has not been investigated for seaweeds and especially under long time scales. We also do not know how abiotic stressors may influence the ‘core’ bacterial species of seaweeds. Following an initial (immediately after field collection, T0) sampling of epibacterial community of an invasive red seaweed Agarophyton vermicullophylum, we conducted a long term mesocosm experiment for 5 months, to examine the influence of three different salinities (low, medium and high) at two different time points (T1, T2) on the epibacterial community richness and composition of Agarophyton. Metagenomic sequencing showed that epibacterial communities changed significantly according to salinity and time points sampled. Epibacterial richness was significantly different between low and high salinities at both time points. Epibacterial richness also varied significantly among T1 and T2 within low, medium and high salinity level. Irrespective of salinity levels and time points sampled 727 taxa consistently appeared in all Agarophyton samples hinting at the presence of core bacterial species on the surface of the alga. Our results indicate that both salinity and time can be major driving forces in structuring epibacterial communities of seaweeds with respect to richness and β diversity. We highlight the necessity of conducting long term experiments allowing us to detect and understand epibacterial succession over time on seaweeds.